Tell me where you live and I'll tell you who you are: Spatial segregation of southern species of Eligmodontia Cuvier in Patagonia, Argentina - Ruiz Barlett, Trinidad (2020)
Fil: Abramson, Guillermo Comisión Nacional de Energía Atómica. Instituto Balseiro, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina